Effects of competition and bundled payment on the performance of hip replacement surgery in Stockholm, Sweden: results from a quasi-experimental study - Fanny Goude; Göran Garellick; Clas Rehnberg; Mikko Peltola; Henrik Malchau; Sverre Kittelsen (BMJ Open)
Objective To evaluate the effects of competition and a bundled payment model on the performance of hip replacement surgery.Design A quasi-experimental study where a difference-in-differences analytical framework is applied to analyse routinely collected patient-level data from multiple registers.Setting Hospitals providing hip replacement surgery in Sweden.Participants The study included patients who underwent elective primary total hip replacement due to osteoarthritis from 2005 to 2012. The final study sample consisted of 85 275 hip replacement surgeries, where the exposure group consisted of 14 570 surgeries (n=6380 prereform and n=8190 postreform) and the control group consisted of 70 705 surgeries (n=32 799 prereform and n=37 906 postreform).Intervention A reform involving patient choice, free entry of new providers and a bundled payment model for hip replacement surgery, which came into force in 2009 in Region Stockholm, Sweden.Outcome measures Performance is measured as length of stay of the surgical admission, adverse event rate within 90 days following surgery and patient satisfaction 1 year postsurgery.Results The reform successfully improved the adverse event rate (1.6 percentage reduction, p<0.05). Length of stay decreased less in the more competitive market than in the control group (0.7 days lower, p<0.01). These effects were mainly driven by university and central hospitals. No effects of the reform on patient satisfaction were found (no significance).Conclusions The study concludes that the incentives of the reform focusing on avoidance of adverse events have a predictable impact. Since the payment for providers is fixed per case, the impact on resource use is limited. Our findings contribute to the general knowledge about the effects of financial incentives and market-oriented reforms.